2018
DOI: 10.1200/jgo.18.10350
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Mammography Screening in Nigeria: A Survey of Two Communities With Different Access to Screening Facilities

Abstract: Purpose Breast cancer outcomes are poor in most low- and middle-income countries. This is a result, in part, of delayed presentation. Critical to improving this gloomy picture is the promotion of breast cancer screening programs; however, designing a formidable screening program requires obtaining necessary background data. This survey evaluates breast cancer screening practices and barriers in two Nigerian communities with different geographic access to screening facilities. Methods We administered a 35-item … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…20 Only 2.3% of women reported ever having had a mammogram. 21 As population-based screening is impractical in most resourcelimited settings, interventions should be aimed toward timely presentation and earlier diagnosis of clinically apparent disease. 22 Screening directed at high-risk populations is one potential strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Only 2.3% of women reported ever having had a mammogram. 21 As population-based screening is impractical in most resourcelimited settings, interventions should be aimed toward timely presentation and earlier diagnosis of clinically apparent disease. 22 Screening directed at high-risk populations is one potential strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent survey of over a thousand women in a Nigerian community, only about 20% of the women had ever had a clinical breast examination, the majority not in the last 1 year 20 . Only 2.3% of women reported ever having had a mammogram 21 …”
Section: Discussionmentioning
confidence: 99%
“… 13 Also, it has been recommended that women start routine screening at 40 to 44 years of age. 14 However, previous studies indicated that BCS uptake is deficient in Nigerian women. 15 , 16 For instance, a study 17 reported that only 3% of women who qualified for annual screening had undergone mammographic screening, while another study reported that only 27.4% participated in CBE.…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 For instance, a study 17 reported that only 3% of women who qualified for annual screening had undergone mammographic screening, while another study reported that only 27.4% participated in CBE. 14 Despite the benefits of BCS, many factors influence its uptake among Nigerian women. Such factors include women’s personal or demographic characteristics, fear of screening outcome, lack of capacity (self-efficacy), ignorance, healthcare-related factors, poverty, and cost of screening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation